Study on the Inhibition of Mild Steel Corrosion by Cationic Gemini Surfactant in 1 M HCl. Issue 7 (2nd July 2016) - Mobin, M.; Aslam, Jeenat; Al-Lohedan, Hamad A.
Abstract : The cationic gemini surfactant 1, 2-bis( N -tetradecyl- N, N -dimethylammonium)ethane dibromide (14-2-14) was synthesized using a previously described method. The surfactant was characterized using 1 H NMR. The corrosion inhibition effect of 14-2-14 on mild steel in 1 M HCl at temperatures 30–60°C was studied using weight loss measurements, potentiodynamic polarization measurements and electrochemical impedance spectroscopy. Morphology of the corroded mild steel specimens was examined using scanning electron microscopy (SEM). The results of the studies show that gemini surfactant is an efficient inhibitor for mild steel corrosion in 1 M HCl; the maximum inhibition efficiency (IE) of 98.06% is observed at surfactant concentration of 100 ppm at 60°C. The %IE increases with the increasing inhibitor concentration and temperature. The adsorption of inhibitor on the mild steel surface obeys Langmuir adsorption isotherm. SEM studies confirmed smoother surface for inhibited mild steel specimen. GRAPHICAL ABSTRACT: